2009
DOI: 10.4141/cjps09022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and molecular markers associated with multi-gynoecia (Mg) gene in Trigrain whea

Abstract: Trigrain wheat normally produces up to three gynoecia in a single floret and forms three close-set grains. The gene conferring the multi grain phenotype was earlier designated Mg, the multiple gynoecia gene. Different genetic patterns controlling this trait have been reported. In the present work we studied the inheritance of the three grains trait and identified simple sequence repeats (SSR) markers linked to the Mg gene. Segregation analysis in the cross IGDB-TW (trigrain wheat)/Chinese Spring confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…However, the gene 12TP showed a dosage effect, indicating that a semi-dominant gene rather than a dominant gene. This result differs from all previously described wheat multi-pistil mutants reported before, including Pis1 and Mg (Peng et al 2008;Wang et al 2009). Our results indicated that 12TP is a novel multi-pistil gene.…”
Section: Tp Has Dosage Effectcontrasting
confidence: 99%
See 4 more Smart Citations
“…However, the gene 12TP showed a dosage effect, indicating that a semi-dominant gene rather than a dominant gene. This result differs from all previously described wheat multi-pistil mutants reported before, including Pis1 and Mg (Peng et al 2008;Wang et al 2009). Our results indicated that 12TP is a novel multi-pistil gene.…”
Section: Tp Has Dosage Effectcontrasting
confidence: 99%
“…There were two multi-pistil genes, Pis1 and Mg, have been previously located on 2DL. Both Pis1 and Mg were in the middle region of the SSR markers Xgwm539 and Xgwm349 (Peng et al 2008;Wang et al 2009). Yang et al (2017) constructed a high-density linkage map of wheat using GBS-SNP data, and found that the Pis1 was located in a 4.1-cM region flanked by the SNP markers M70 and M71.…”
Section: Multi-pistil Gene 12tp Is Also On 2dlmentioning
confidence: 99%
See 3 more Smart Citations